Detection of carbapenem resistance genes in Pseudomonas aeruginosa isolates with several phenotypic susceptibility profiles - Morales, Sara; Gallego, Marlon A; Vanegas, Johanna M; Jiménez, J Natalia (CES Medicina, 2018)
Introduction: Pseudomonas aeruginosa display several resistance mechanisms to carbapenems and such variety makes it difficult to infer from the antibiogram. The aim of this study was to determine the carbapenem resistance genes in P. aeruginosa isolates with different profiles of phenotypic susceptibility to these antibiotics. Materials and methods: From a microbial collection of P. aeruginosa isolates from infected patients, 40 isolates with different carbapenem resistance profiles were selected. The carbapenemases genes, and expression of the OprD porin, the MexAB-OprM efflux pump and the β-lactamase AmpC were determined. Results: From a total of 40 isolates evaluted, in 21 (52.5%) any mechanism of resistance evaluated were detected. In the meropenem-resistant group, overexpression of AmpC (n = 1) and decreased expression of MexAB-OprM (n = 2) and OprD (n = 1) were found. A decrease in the expression of MexAB-OprM was observed in imipenem-resistant group (n = 3) and mutations in the gene encoding the OprD porin (n = 1). Finally, the presence of carbapenemases (VIM, n= 3, KPC-2 / VIM, n = 1) was detected in imipenem-meropenem resistant isolates. Conclusion: The phenotypic susceptibility profiles in P. aeruginosa isolates were not explained by the molecular mechanisms explored, with the exception of carbapenemase-producing isolates. These results evidence the complexity of the antibiotic resistance mechanisms involved in this bacterium.